Laos: Beyond the Revolution
XIX, 348 p.
Keywords: This work contains papers presented at a conference called "Current Developments in Laos" in Washington DC in 1988. The topics covered range from Lao nationalism and American policy, 1954-1959, to Laotian refugees in Thailand.